Peningkatan Sumberdaya Manusia Melalui Gedangsari Festival - Mulasari, Surahma Asti; Wibowo, Muh Waldami Dwi; Irjayanti, Azizah; Nurmalasari, Elsa (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2019)
The implementation of the Regular Community Service (KKN Reguler) is carried out in the context of applying oneof the Tri Dharma of Higher Education, namely community service. Division XIV, XV, and XVI of Regular LXXI UADKKN are committed to serving the community with several planned work programs that aim to increase the potentialof community resources in the villages of Hargomulyo, Serut, Sampang, Watu Gajah, and Mertelu, GedangsariDistrict. Community empowerment seeks to improve the quality of human resources (HR), especially in shapingand changing people’s behavior to achieve a better life and a better quality of life. In order to explore the potentialof Gedangsari District, LXXI UAD Regular KKN holds Gedangsari Festival activities which are expected to become amedium to explore the potential of the community and can improve the quality of human resources from childrento adults in Gedangsari District, Gunung Kidul Regency.